2015
DOI: 10.1007/s00775-015-1242-x
|View full text |Cite
|
Sign up to set email alerts
|

In vitro effects of binuclear (η 6-p-cymene)ruthenium(II) complex containing bridging bis(nicotinate)-polyethylene glycol ester ligand on differentiation pathways of murine Th lymphocytes activated by T cell mitogen

Abstract: T cell differentiation into distinct T helper (Th) subpopulations is crucial in governing acquired immune responses as well as some inflammatory and autoimmune disorders. This study investigated potential of the novel neutral binuclear ruthenium(II) complexes 1-8 with general formula [{RuCl2(η(6)-p-cym)}2μ-(N(∩)N)] (N(∩)N = bis(nicotinate)- and bis(iso-nicotinate)-polyethylene glycol esters; (3-py)COO(CH2CH2O) n CO(3-py) and (4-py)COO(CH2CH2O) n CO(4-py); n = 1-4), as well as [RuCl2(η(6)-p-cym)(nic)] (R1, nic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…Several complexes of a series of pyridine- and imidazole-substituted Ru complexes were even more active as compared to rapamycin in blocking TCR-mediated lymphocyte stimulation in the very low nanomolar range . A binuclear (η 6 -p-cymene)­Ru­(II) complex containing a bridging bis­(nicotinate)-polyethylene glycol ester ligand inhibited proinflammatory T H 1/T H 17 cell differentiation and induced a T reg phenotype characterized by IL-4 and IL-10 production . Furthermore, the Ru­(II) complex cis-[Ru­(II)­(η 2 - O 2 CR)­(dppm) 2 ]­PF 6 (R = H or (CH 2 ) 4 COOEt) (Figure F) was developed as an anti- Leishmania agent based on the iron (Fe)-mimetic properties of the Ru core and showed high antiparasitic activity.…”
Section: Immunological Effects Of Specific Metal Drugsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several complexes of a series of pyridine- and imidazole-substituted Ru complexes were even more active as compared to rapamycin in blocking TCR-mediated lymphocyte stimulation in the very low nanomolar range . A binuclear (η 6 -p-cymene)­Ru­(II) complex containing a bridging bis­(nicotinate)-polyethylene glycol ester ligand inhibited proinflammatory T H 1/T H 17 cell differentiation and induced a T reg phenotype characterized by IL-4 and IL-10 production . Furthermore, the Ru­(II) complex cis-[Ru­(II)­(η 2 - O 2 CR)­(dppm) 2 ]­PF 6 (R = H or (CH 2 ) 4 COOEt) (Figure F) was developed as an anti- Leishmania agent based on the iron (Fe)-mimetic properties of the Ru core and showed high antiparasitic activity.…”
Section: Immunological Effects Of Specific Metal Drugsmentioning
confidence: 99%
“…428 Nevertheless, the nature of the metal drugs seems to be crucial, as, for example, a binuclear (η 6 -p-cymene)Ru(II) complex containing a bridging bis(nicotinate)-polyethylene glycol ester ligand was enhancing differentiation of T cells toward a T reg phenotype (compare section 3.3). 429 With regard to clinical data, multiple studies have indicated that, although in some cases the absolute number of T cells was reduced, an enhanced ratio CTL/T reg 430 and/or a reduced number of tumor-resident MDSC 431 was observed (compare section 8.2). This strongly supports reduced CTL deactivation and induction of a permissive TME based on the preferential killing of regulatory immune cells by anticancer metal therapy also in the clinical situation.…”
Section: Anticancer Metal Drugs and The Immunementioning
confidence: 99%
“…In our study, the level of CD8 + corresponded to the production of IFN-c and IL-10. CD4 is a co-receptor that assists the TCR in communicating with an antigen-presenting cell, and CD4 + cell could be divided into helper T cell (Th), inducer T cell (T I ), and delayed type hypersensitivity T cell (T D ) (Momcilovic et al 2015). Meanwhile, IFN-c is usually to be considered as marks of Th1 immune response (Zhu et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…www.advancedsciencenews.com www.advtherap.com The most promising results were obtained with vascular endothelial growth factor receptor 1 (VEGFR1) and 2 (VEGFR2) peptides. [136] The application of so-called carbon monoxide-releasing complexes triggers the release of CO, which directly activates antiinflammatory effects in immune cells, leading to an anticancer effect. CTL responses to VEGFR1 and VEGFR2 were also significantly increased in the HLA-matched group.…”
Section: How To Benefit From and With Immunotherapy?mentioning
confidence: 99%
“…The anti‐angiogenic properties of Ru‐complexes containing 2,6‐ bis (benzimidazolyl)pyridine, for example, [Ru(bbp)(p‐mpip)Cl]ClO 4, were associated with the downregulation of VEGF downstream signaling, mainly by blocking the binding of VEGF to VEGFR2 . Moreover, it has been demonstrated that ruthenium drugs influence T cell stimulation, by diminishing T cell receptor mediated T cell stimulation or by inducing a Treg‐like phenotype in pro‐inflammatory T H 1/T H 17 cells …”
Section: How To Benefit From and With Immunotherapy?mentioning
confidence: 99%